PENINGKATAN HASIL BELAJAR BAHASA INDONESIA MATERI DRAMA KEHIDUPAN MELALUI METODE BERMAIN PERAN (ROLE PLAYING) - *, Widiasih (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2020)
Indonesian language has a very important position, namely: As a National Language, and as a State Language. That is why in elementary schools, junior high schools, to universities, Indonesian is a subject that must be mastered. This study aims to determine the effectiveness of the role playing method on the learning outcomes of Indonesian in the remaining junior high schools in Kampak District. Researchers used classroom action research in class VIII through two stages of the cycle. The results show that there are differences in learning outcomes. Where the results are better when the teacher uses the role playing method in Indonesian language learning.